2011
DOI: 10.4081/ija.2011.e28
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient flows in lowland dairy farms in the Italian Alps

Abstract: A traditional dairy production system is still common today in the mountain environment of the Italian Alps, enhancing the economic valorisation of milk through the production of quality cheese such as Fontina PDO (Protected Designation of Origin), and favouring the agroenvironmental management of marginal areas. This type of dairy system depends mainly on summer grazing: farmers set up the farm stock on the basis of the high-altitude grassland areas available. For the rest of the year, the livestock is housed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Otherwise Haas et al (2001) in a similar study found that GHG emissions for extensive dairy system are lower than in the intensive one per unit of produced milk (1.0 vs 1.3 t CO2 eq/t milk), and per area (7.0 vs 9.4 t CO2 eq/ha) this due mainly to mineral nitrogen fertiliser renounce. Farms with high feed self-sufficiency had significantly lower acidification potential than the others (Penati et al, 2013) and this is also showed in the works where N and P surplus at the farm-gate is assessed: the most important item of N and P inputs was represented by purchased feeds and hay (Penati et al, 2008;Bassanino et al, 2011). All the considered studies have investigated the sustainability of Alpine livestock farms in terms of environmental impact.…”
Section: Greenhouse Gases Emission and Carbon Sequestration Of Foragementioning
confidence: 87%
“…Otherwise Haas et al (2001) in a similar study found that GHG emissions for extensive dairy system are lower than in the intensive one per unit of produced milk (1.0 vs 1.3 t CO2 eq/t milk), and per area (7.0 vs 9.4 t CO2 eq/ha) this due mainly to mineral nitrogen fertiliser renounce. Farms with high feed self-sufficiency had significantly lower acidification potential than the others (Penati et al, 2013) and this is also showed in the works where N and P surplus at the farm-gate is assessed: the most important item of N and P inputs was represented by purchased feeds and hay (Penati et al, 2008;Bassanino et al, 2011). All the considered studies have investigated the sustainability of Alpine livestock farms in terms of environmental impact.…”
Section: Greenhouse Gases Emission and Carbon Sequestration Of Foragementioning
confidence: 87%
“…Results indicated that 5 out of 7 studies that merged more than 4 different methodological techniques are related to dairy cases. This might be due, in part, to the fact that the dairy production analysis usually occurs in traditional production systems with specific agri-environmental conditions, and which require, given the limitations of their territory, an analysis of the sustainability of agrifood landscapes, as well as to elucidate around critical points management throughout production processes, energy use, or even regulatory and institutional frameworks that might affect these forms of production under PDO protection (Bassanino et al, 2011;Coelho et al, 2017).…”
Section: Methodologies Approaches Used To Study Sustainability In Pdosmentioning
confidence: 99%
“…tion between environmental circumstances and the social and economic sustainability of the activity. For example, in Bassanino et al (2011) an evaluation of the nutrients (nitrogen and phosphorus) of lowland summer pastures in the Valle d'Aosta region was made. The purpose of this evaluation is to measure nutrients so that when farmers buy fodder for their cattle during the winter, they seek to match the amounts of nutrients from summer pastures to obtain the raw material for the dairy final product.…”
Section: Dairymentioning
confidence: 99%